Running-room in the mangle of practice : contemporary art in the thick of things : a thesis presented in partial fulfillment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Shepherd, Richard; Shepherd, Richard (Massey University, 2011)
This document and the exhibited artwork it accompanies aims to perform a positive aesthetic of exile that enacts the dislocating and shattering strategies of spatial, temporal and imagistic montage but also attempts to open a caesura in today’s relentless flow of images and thickening temporality. It joins with particular currents in engaged contemporary art to re-imagine what documentary form might be as an act of revelation not reduction. I have advocated in word and deed a structure of desire that is promiscuous without being possessive and accounts for a mode of subjectivity that temporally emerges from its material conditions in the thick of things. The corpus of experimental work has traversed a wide range of media and intentions but always with these issues in mind. I have produced small, tentative gestures in the city and ambitious proposals for affective maps in a mixed-media installation. I have gathered together an ambitious chorus of voices from across disciplines to share in common in a dialectical movement of resistance and accommodation that seeks to expand the realms of conceptual and corporeal possibility.
Keywords: Space and time in art; Art installations; Conceptual art